Immunological assessment and homogeneity of commercial inactivated bivalent Newcastle and avian influenza H9N2 vaccines in broilers - Zena T. Younis; Fanar A. Isihak (Iraqi Journal of Veterinary Sciences)
Our study aimed to evaluate the immune response of 7 types of bivalent inactivated vaccines. 225 chicks were distributed into 9 groups, groups from 1 to 7; vaccinated on 1 day with different doses of these vaccines against Newcastle Disease Virus-Avian Influenza Virus-H9N2 subcutaneously according to the direction of producers as follows: G1 vaccinated by PRO-VACTM AINK. G2 immunized by Poul Shot® flu H9N2+ ND. G3 received QVAC ND-H9. G4 injected with MEFLUVACTM H9ND7. G5 was immunized with CEVAC® NEW FLU H9 K. G6 received Nobilis N9H2+ND P. G7 was vaccinated with Gallimune. G8 was considered as the positive control group, while G9 was a negative control group. Subsequently, all groups of the experiment except (G9) were vaccinated by eye drop with the live attenuated vaccine (Nobilis® ND Clone-30) at 1 and 14-day-old chicks. The results of the ELISA and HI tests of antibodies titer to ND antigen have varied between groups, and the high titer was observed in G3 and G2 at 28 and 35 days. The lowest and highest titers were detected in G6 and G4 when these titers were measured by general and specific ELISA for AI. Most of the vaccinated groups (G1 to G7) revealed high to moderate expression of CD19 memory B-cells by immunohistochemical staining. In conclusion, most of the tested vaccines in this research gave a sufficient number of antibodies to ND antigen, whereas, in contrast to the AI antigen, many of these vaccines demonstrated a weak antibodies response, except with the G6 vaccine.